Pulse amplitude-modulated time-based interface for off-chip interconnect. Issue 1 (2nd January 2017) - Rashdan, Mostafa
ABSTRACT: An increased number of bits pulse amplitude-modulated differential-time signalling interface for off-chip interconnect is introduced in this article by combining the differential time signalling (DTS) technique with the pulse amplitude-modulation (PAM) approach. Applying the PAM to the DTS-transmitted signal increases the total number of the transmitted bits per symbol while maintaining the transmitted signal bandwidth. 4-bit 6 Gb/s DTS serial link has been designed and simulated using 65 nm CMOS mixed signal technology. 5-bit 7.5 Gb/s and 6-bit 9 Gb/s amplitude-modulated DTS serial links have been designed, simulated and compared to the 6 Gb/s DTS serial link. The three serial links use 1.5 Gb/s as input clock signal. In the amplitude-modulated DTS-transmitted signal, the rising and falling edges of the input clock signal are modulated in time as well as the transmitted signal amplitude is modulated. A reference clock pulse is generated from the input clock signal and embedded on the transmitted signal to be used as reference timing at the receiver circuit. The design details of the designed links are presented in the article. The 9 Gb/s link uses a 60 cm 4003C Rogers substrate as a transmission channel. The transmitted signal spectrum is presented and compared for the three designed links. The total power consumption of the 9 Gb/s amplitude-modulated DTS interface is less than 25 mW.